FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEPEMILIKAN JAMBAN DI DESA BANGUN PURBA KECAMATAN BANGUN PURBA - Andria Andria Andria; Sri Wulandari (Jurnal Ilmu Kebidanan, 2021)
Environmental problems today are indeed the most common problems in the environment, namely pollution, unhygienic ways of managing food, low levels of clean and healthy living (PHBS) and lack of clean water and healthy latrines. The latrine is a place for human waste disposal but there are still many people who do not dispose of their waste properly. The behavior of defecating (BAB) in any place and tends not to use the latrine is one of the habits that individuals have as a result of imitating the behavior of the people around them. Based on data from the Central Statistics Agency (BPS) in Rokan Hulu Regency, 9.61% did not use defecation facilities. The purpose of this study was to determine the factors that influence the ownership of latrines in Bangun Purba Village, Bangun Purba District. The method used was descriptive analytic with cross sectional design. The sample in this study amounted to 60 people. The sampling technique used is simple random sampling. Analysis of the data used is univariate analysis which performs univariable analysis and also bivariate analysis which performs statistical tests using the chi-square test. The results showed that there was a relationship of knowledge to the use of latrines in Bangun Purba Village with a p value of 0.001, there was a relationship between education and the use of latrines in Bangun Purba Village with a p value of 0.004, and there was a relationship between the role of health workers on the ownership of latrines in Bangun Village. Ancient with p value = 0.003. The conclusion is that there is a significant relationship between knowledge, education, and the role of health workers on latrine ownership. Suggestions need for counseling about the importance of latrines that are useful for maintaining public health and the environment.